Risk and Protective Factors in Ecuadorian Adolescent Survivors of Suicide - Marly Johana Bahamón; José Julián Javela; Stefano Vinaccia; Shadye Matar-Khalil; Andrés Cabezas-Corcione; Evelyn Esther Cuesta (MDPI AG, 2023)
Suicide is one of the main causes of death among the adolescent population, which is why it is considered an important mental-health problem. In addition to this situation, for each suicide, the group of people who survive it (known as suicide survivors) can present serious emotional affectations, becoming a population at risk for this problem. The purpose of this study was to analyze the effect of suicide-survivor status on risk factors and protective factors for suicide. A total of 440 adolescents with a mean age of 15.78 (SD = 1.74) participated, who were divided according to survivor status, identified as the SV group (79 cases), and non-survivors, identified as the NSV group-adolescents that did not have experience or contact with a suicide attempt (361 cases). A questionnaire of sociodemographic characterization and risk conditions, the Alexian Brother Urge to Self-Injure (ABUSI), the Plutchik Suicide Risk Scale, the Multidimensional Scale of Perceived Social Support, and the Cognitive and Affective Empathy Test (TECA) were applied. Descriptive statistics, mean difference for independent samples, contingency tables, X2 statistic, Fisher's exact statistic, and Cohen's d coefficient were used. The results show significant differences between SV and NSV participants in risk and protective factors regarding the presence of a greater adoption of perspective and emotional understanding. On the other hand, NSV adolescents presented higher scores of perceived social supports regarding risk factors, and there was a higher proportion of a history of suicide attempt, severity/hospitalization, impulse to self-harm, and level of suicidal risk in the SV group. The need to incorporate forms of suicide prevention with the survivor population is discussed, increasing the possibilities of postvention.